2007
DOI: 10.1029/2007jd008834
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the agricultural Green Revolution–induced land use changes on air temperatures in India

Abstract: [1] India has one of the most intensive and spatially extensive irrigation systems in the world developed during the1960s under the agricultural Green Revolution (GR). Irrigated landscapes can alter the regional surface energy balance and its associated temperature, humidity, and climate features. The main objective of this study is to determine the impacts of increased irrigation on long-term temperature trends. An analysis of the monthly climatological surface data sets at the regional level over India showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 63 publications
(85 reference statements)
3
80
1
Order By: Relevance
“…These results are consistent with a number of studies that show that agricultural areas are often associated with negative trends in irrigated areas (e.g. Christy et al, 2006;Mahmood et al, 2006;Roy et al, 2007;Lobell and Bonfils, 2008) as well as in rainfed croplands (McPherson et al, 2004).…”
Section: Observation Reanalysis and Omr Trendssupporting
confidence: 81%
See 2 more Smart Citations
“…These results are consistent with a number of studies that show that agricultural areas are often associated with negative trends in irrigated areas (e.g. Christy et al, 2006;Mahmood et al, 2006;Roy et al, 2007;Lobell and Bonfils, 2008) as well as in rainfed croplands (McPherson et al, 2004).…”
Section: Observation Reanalysis and Omr Trendssupporting
confidence: 81%
“…Consequently, attention has been increasingly given to the impact of LULC change on climate. For example, it has been reported that land use changes due to agriculture lead to decreased surface temperatures (Mahmood et al, 2006;Roy et al, 2007;Lobell and Bonfils, 2008). LULC change can significantly influence climatological variables such as maximum, minimum and diurnal temperature range (Gallo et al, 1996;Hale et al, 2006Hale et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plausible cause for these negative CC values is an increase in rainfall activity by warm monsoon clouds (Kandalgaonkar et al, 2005). They also indicate a lower ocean-continent thermal contrast that motivates a greater entrance of humidity, therefore the occurrence of convective rain during the monsoon season (Roy et al 2007). In addition, an increase of accumulated daily rainfall at the beginning and end of the monsoon season has been observed (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the analysis, it is seen that the urbanization effects on temperature is not uniform at all the stations. It may be due to location of stations, spatial temperature variability, aerosol optical depth over that region as well as agricultural cropping patterns [24]. In the recent period, both maximum and minimum temperatures show a significant increasing trend at 5 stations, but the stations at which both temperatures show a significant increasing trend are very few (2 stations) and they are located in Southern part of India.…”
Section: Medium Citiesmentioning
confidence: 96%